The Effectiveness of Family-based Neuropsychological intervention program on Executive Functions of Children with Attention Deficit/Hyperactivity Disorder - Negin Motamed Yeganeh; Gholam Ali Afrooz; Mohsen Shokoohi Yekta; Rachel Weber (Ravānshināsī-i Afrād-i Istis̠nāyī, 2020)
Attention Deficit/Hyperactivity Disorder is one of the most common neurodevelopmental disorders in childhood. These children are exposed to a lot of problems in the executive functions areas. The issue of neuroplasticity reveals the importance of neuropsychological interventions, since interruptions in early childhood executive functions may lead to further functional impairment. Therefore, this study was conducted to evaluate the effectiveness of the designed intervention program on the Executive functions of children with Attention Deficit/Hyperactivity Disorder. The research method was quasi-experimental with a pretest-posttest-follow up design with the control group. The statistical population of the present study included all the boys and girls students 7-10 years old in Tehran. Among eligible students, 40 individuals along with their mothers were selected using the non-random purposive sampling method and randomly divided into the two groups. The experimental group (N=20) were trained by twelve sessions of Metacognitive Executive Functioning intervention program and the control group (N=20) remained on the waiting list. Data were collected by Clinical interview checklist, the Tehran Stanford-Binet intelligence test and Behavior Rating Inventory of Executive Functions. The results indicated a significant effect of Family-based Neuropsychological program on increasing the Executive Functions of children with Attention Deficit/ Hyperactivity Disorder (p<0.05). This treatment can be a potentially promising intervention for young children with ADHD.